2003
DOI: 10.18553/jmcp.2003.9.3.248
|View full text |Cite
|
Sign up to set email alerts
|

Examination of Resource Use and Clinical Interventions Associated With Chronic Kidney Disease in a Managed Care Population

Abstract: BACKGROUND: The management of chronic kidney disease (CKD) is multifaceted, including monitoring, early diagnosis, and treatment of comorbidities such as diabetes, hypoalbuminemia, and anemia, and initiating timely procedures in preparation for dialysis such as vascular access placement. Presumably, optimal care provided to patients during the predialysis phase will produce a significant impact on morbidity and mortality outcomes.OBJECTIVE: A retrospective analysis was conducted to assess specific factors that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…More than half of the anaemic patients (59%) received some type of treatment for anaemia. The low rates of anaemia treatment in the clinical setting that we observed are consistent with results from various surveys showing undertreatment or suboptimal treatment of anaemia in patients with CKD [32][33][34][35][36] .…”
Section: Discussionsupporting
confidence: 90%
“…More than half of the anaemic patients (59%) received some type of treatment for anaemia. The low rates of anaemia treatment in the clinical setting that we observed are consistent with results from various surveys showing undertreatment or suboptimal treatment of anaemia in patients with CKD [32][33][34][35][36] .…”
Section: Discussionsupporting
confidence: 90%
“…Importantly, patients with medication discrepancies are more likely to be readmitted (19). In addition, established practices for kidney disease management are vastly underused (20)(21)(22)(23). A recent survey of internal medicine residents found deficits in almost every domain of knowledge about CKD complications and management (24).…”
Section: Discussionmentioning
confidence: 99%
“…However, on evaluation of USRDS data, the difference between all-cause hospitalization rates and hospital days amongst ESRD patients aged 75 or older (2.142 admissions/PYAR, and 15.9 days/PYAR), and patients aged 65–74 (1.973 admissions/PYAR and 15.0 days/PYAR) was only 0.169 admissions/PYAR and 0.9 days/PYAR, respectively [2]. Although comparative data on hospitalization rates in patients with earlier stages of CKD among various age groups were not available for evaluation, in a study of pre-dialysis patients 67% of the patients with a mean age of 67 years were reported to be hospitalized during the 12-month period leading to dialysis [21], thus confirming a higher hospitalization rate in this population. The DRG Handbook is drawn from a large population and is a good approximation for total hospitalization costs, but it does not make a designation for patients with comorbidities.…”
Section: Discussionmentioning
confidence: 99%